Ultrahigh-Strain-Rate Mechanical Properties of Polystyrene near the Glass Transition Temperature - Anuraag Gangineri Padmanaban; Takumi Uchiyama; Jonathan P. Rothstein; James J. Watkins; Jae-Hwang Lee (Applied Sciences, 2025)
Elastoplastic and tribological characteristics of polystyrene are investigated as a model glassy polymer at the ultrahigh-strain rate (>106 s −1) through the temperature-controlled laser-induced particle impact testing (LIPIT) technique. Polystyrene (PS) microparticles with a diameter of 44 µm are subjected to collisions on a rigid surface at speeds ranging from 200 to 600 m s−1, while the temperature is systematically varied between room temperature and 140 °C. Utilizing the flight path and rebound motion measured from 45-degree angled LIPIT experiments, the coefficients of restitution and dynamic friction are quantified with vectorial analysis. The onset of inelasticity can be possible at a temperature substantially lower than Tg due to the early onset of crazing dominance. While temperature- and velocity-dependent coefficients of friction suggest that the activated surface of PS can facilitate the consolidation of PS microparticles, the enhancement effect is expected more profoundly when the temperature exceeds the glass transition temperature. The microscopic ballistic approach with controlled temperature demonstrates its capability of systematically evaluating the temperature effects on various inelastic deformation mechanisms of polymers at the ultrahigh-strain-rate regime.